Essential oils from pequi fruits from the brazilian Cerrado ecosystem - Geőcze, K. C.; Barbosa, L. C. A.; Fidêncio, P. H.; Silvério, F. O.; Lima, C. F.; Barbosa, M. C. A.; Ismail, Fyaz M. D. (Food Research International, 2013)
The composition of the essential oils of pequi fruits gathered from the Brazilian Cerrado ecosystem in the states of Maranhão (MA), Minas Gerais (MG) and Tocantins (TO) was investigated. The oils were obtained by steam distillation, and each component was speciated using GC-MS. The oil content varied from 0.13% to 1.15%. Interestingly, the major substance found within samples from two of the states was ethyl hexanoate (MA, MG), whereas isopropyl hexanoate and isopentyl-2-methylbutanoate were specific for the samples from TO. Both principal components analysis (PCA) and hierarchical cluster analysis (HCA) were used for exploratory analysis of the oils, and, consequently, the pequi fruits were classified according to their place of origin. The PCA showed that 51.5% of the variance accumulated in the PC1 and PC3, and the group formation obtained using HCA confirmed that the oil composition is influenced by geographic and/or plant genetic factors. Such analyses could assist in the selection of more flavoursome and healthy variants of pequi.
Keywords: Caryocar brasiliense; Aroma volatiles; Pequi; GC-MS; PCA and HCA; Ethyl hexanoate